Overview of test methods used to classify wheat flour and bread samples – REVIEW - Baráth, Nikolett; Ungai, Diána Kinga; Kovács, Béla (Acta Agraria Debreceniensis, 2023)
In Hungary, common wheat (Triticum aestivum ssp. vulgare) is of good quality and world famous. In addition, it plays an important role in the human diet. The classification of flours ground from wheat is quite decisive and there are several methods for its examination. The most important flour testing requirements include moisture content, protein content gluten properties and the most important bakery value number. The measured characteristics give us the opportunity to conclude about the properties of the dough, and then bakery products. Several dynamic and static methods have been developed to study the physical properties of dough. The evaluation of products can be carried out in several respects with the help of a baking test. The multitude of methods currently used to qualify flour, dough and finished products also proves that the overview of the methods is quite topical.